2018
DOI: 10.1071/sr16357
|View full text |Cite
|
Sign up to set email alerts
|

Soil biochemical changes at different wheat growth stages in response to conservation agriculture practices in a rice-wheat system of north-western India

Abstract: Intensive tillage, removal or burning of crop residues, limited organic manure use, declining irrigation water resources and scarcity of labour are the major causes of soil degradation and unsustainability of rice (Oryza sativa L.)–wheat (Triticum aestivum L.) system (RWS) in South Asia.Resource conservation technologies (RCTs) such as zero tillage (ZT), dry direct seeded rice (DSR) and crop residues retained as mulch have shown promise to increase the productivity and profitability of RWS in South Asia. Effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 54 publications
4
22
0
Order By: Relevance
“…A particular trend of ARS activity was recorded irrespective of scenarios, highest at tillering and lowest at harvesting, it may be due to the effect of crop growth stage. Such type of result is also reported by Bera et al (2017) who reported higher enzyme activity at the vigorous vegetative growth stages (such as maximum tillering and jointing stages) than at the reproductive growth stages (such as grain filling and maturity stages). It was 14 per cent higher in CSA systems (Sc2-Sc6) than farmer's practice.…”
Section: Arylsulphatasesupporting
confidence: 83%
“…A particular trend of ARS activity was recorded irrespective of scenarios, highest at tillering and lowest at harvesting, it may be due to the effect of crop growth stage. Such type of result is also reported by Bera et al (2017) who reported higher enzyme activity at the vigorous vegetative growth stages (such as maximum tillering and jointing stages) than at the reproductive growth stages (such as grain filling and maturity stages). It was 14 per cent higher in CSA systems (Sc2-Sc6) than farmer's practice.…”
Section: Arylsulphatasesupporting
confidence: 83%
“…The soil microbial properties respond quickly and significantly to change in tillage 61 , crop establishment techniques 29 , 62 , fertilization 63 and external inoculation of microbial culture 64 . In the present study, microbial consortia involving cyanobacteria for nitrogen fixation and bacteria for P solubilization were used.…”
Section: Discussionmentioning
confidence: 99%
“…These CETs have varied levels of impact on soil properties, plants performance and nutrient and water availability 3 , 28 , 29 . Such impacts can act as a guide for modulating the recommendations and input portfolio of crop and/or cropping system.…”
Section: Introductionmentioning
confidence: 99%
“…To address the aforementioned issues, conservation agriculture (CA)-based practices (minimum tillage, residue retention and crop diversi cation) are being developed and promoted for rice and wheat production (Gathala et al, 2013). The alternative systems of tillage, green manure (GM) and residue management practices under CA-based practices can potentially lead to signi cant changes in the availability of nutrients in RWS (Bera et al, 2017;Saikia et al, 2019a). The CA-based practices holds the potential to enhance P availability by altering the soil microbial diversity and enzyme activity, which in turn affects the availability of soil P (Wang et al, 2011;Bhan and Behera 2014;Bezerra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%